(untitled) (FULAFIA IAC Book of Proceedings, 2025)
Africa possesses abundant energy resources, yet distorted energy pricing structures and subsidy policies have hindered investment and economic growth. This study examines the impact of energy pricing and subsidy reforms on investment and economic growth across 29 African countries using the Cross-Sectionally Augmented Autoregressive Distributive Lag (CS-ARDL) technique. The findings reveal that energy subsidies, particularly in gasoline, have significant negative effects on investment in the energy sector and overall economic growth. In the short run, subsidies distort resource allocation and create inefficiencies, while long-term analyses suggest that stable governance and consistent policy reforms can mitigate these distortions. The study further highlights that the impact of energy pricing varies across African nations, necessitating context-specific policy approaches. The results indicate that political stability plays a crucial role in fostering economic growth, while subsidy reductions can enhance fiscal sustainability. Based on these insights, the study recommends a gradual phase-out of energy subsidies, improved governance, and the implementation of targeted social safety nets to ensure equitable economic progress. Such policy measures can attract investments in the energy sector and contribute to long-term economic resilience and sustainable growth in Africa.